2012
DOI: 10.1111/j.1743-6109.2012.02684.x
|View full text |Cite
|
Sign up to set email alerts
|

Is Oral Sex Really a Dangerous Carcinogen? Let’s Take a Closer Look

Abstract: Introduction Questions have recently arisen in the popular press about the association between specific sexual behaviors, namely, fellatio and cunnilingus, with head and neck cancers. Although there has been an overall decline in the incidence of head and neck cancers over the past 25 years, there has been a shift in the distribution of these cancers toward a particular type known as oral squamous cell carcinomas (OSCCs), and a younger demographic. These particular cancers, OSCCs, have been s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 65 publications
(96 reference statements)
1
8
0
2
Order By: Relevance
“…(42) HPV pozitif orofaringeal skuamöz hücreli kanserin cinsel ilişkiye ve artan cinsel partner sayısına bağlantılı olduğunu ancak az cinsel partneri olan birçok bireyde de ortaya çıkabildiğini bildirmiş-tir. Rosenquist (43) bir makalede, serviks kanseri ile ilgili verileri özetlerken HPV ile enfekte olan kadın-ların çoğunda serviko-vajinal enfeksiyonların kendiliğinden ortadan kalktığı, bunun sonucunda serviks kanseri gelişen küçük bir yüzdenin kaldığını belirtmiştir. Böylece serviks kanseri gelişiminde HPV enfeksiyonunun tek faktör olmadığı ortaya konmuştur.…”
Section: -Oral Seks Kanser Gelişiminde Etken Midir?unclassified
See 1 more Smart Citation
“…(42) HPV pozitif orofaringeal skuamöz hücreli kanserin cinsel ilişkiye ve artan cinsel partner sayısına bağlantılı olduğunu ancak az cinsel partneri olan birçok bireyde de ortaya çıkabildiğini bildirmiş-tir. Rosenquist (43) bir makalede, serviks kanseri ile ilgili verileri özetlerken HPV ile enfekte olan kadın-ların çoğunda serviko-vajinal enfeksiyonların kendiliğinden ortadan kalktığı, bunun sonucunda serviks kanseri gelişen küçük bir yüzdenin kaldığını belirtmiştir. Böylece serviks kanseri gelişiminde HPV enfeksiyonunun tek faktör olmadığı ortaya konmuştur.…”
Section: -Oral Seks Kanser Gelişiminde Etken Midir?unclassified
“…(43) oral seks, HPV ve kanser arasındaki bağlantının basit bir neden ve sonuç ilişkisi olmadığı sonucuna varmışlardır. Rosenquist, bir HPV enfeksiyonunun kalıcı hale gelmesi ve daha sonra kanserojen hale gelmesi için birçok faktörün dahil olması gerektiğini vurgulamış, bu faktörlerin bazıla-rının bilinmediği ve olasılıkla bağışıklık sistemi ile ilgili olduğu belirtilmiştir.…”
Section: -Oral Seks Kanser Gelişiminde Etken Midir?unclassified
“…In a provocative article, Rosenquist [8] summarized the data for cervical cancer and noted that the majority of HPV-infected women were able to clear their cervico-vaginal infections spontaneously, leaving only a small percentage subsequently developing cervical cancer; thus making HPV infection a necessary, but not the sole factor, in the development of cervical cancer. She further highlighted several studies that showed that cervico-vaginal HPV infection is predominantly self-limiting with a median duration of 8–12 months.…”
Section: Hpv-positive Opcmentioning
confidence: 99%
“…She further highlighted several studies that showed that cervico-vaginal HPV infection is predominantly self-limiting with a median duration of 8–12 months. In large epidemiological studies, “the risk factors most consistently associated with progression of high-risk HPV to cervical cancer were as follows: high parity (number of children), long-term oral contraceptive use, smoking, and co-infection with other sexually transmitted diseases” [8]. …”
Section: Hpv-positive Opcmentioning
confidence: 99%
See 1 more Smart Citation